Intramuscular Fat Deposition and Osteoarthritis Pathology: A Possible Overlooked Pathogenic Correlate? - Marks Ray (Journal of Aging Research And Healthcare, 2025)
Osteoarthritis, the most prevalent joint disease and one affecting many aging adults is strongly associated with various degrees of disability and high health costs. Commonly deemed largely incurable and progressive, it appears muscle fat deposition and its encroachment on muscle tissue may account for multiple adverse health outcomes, especially the osteoarthritic disease process. This mini review examines whether contemporary evidence supports a role for efforts towards preventing excess fat infiltration into vulnerable muscles as one means of reducing osteoarthritic pain and disability. To this end, research on this theme and reported as of June 2025 on this issue was sought. We found that with few exceptions and regardless of joint examined a role for muscle mass infiltration in osteoarthritis disability appears of high clinical significance.
Keywords: Aging